PEMBERDAYAAN IBU HAMIL MELALUI PEMANFAATAN PANGAN LOKAL SAGU MOCHI ROSELLA (GUCHIRO) SEBAGAI UPAYA PENCEGAHAN ANEMIA - Findy Hindratni (Poltekkes Kemenkes Riau, 2026)
Anemia during pregnancy is a fundamental public health issue due to its high risk to maternal and fetal safety. Interventions using Iron-Folic Acid tablets are often hindered by low compliance caused by side effects. This community engagement program aimed to improve the knowledge and practical skills of pregnant women and health cadres in utilizing local food resources from Riau—specifically the combination of sago and roselle calyx, which are rich in iron and vitamin C—into a healthy food product called